Effect of Square Head Tooltip and Joining Speed on Aluminium Alloy AA6061 in Friction Stir Welding - Bujang, Denilson Owen Anak; Rosli Ahmad (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Friction stir welding (FSW) is a solid-state joining process that gained significant attention in recent years due to its advantages over traditional welding techniques. FSW utilizes non-consumable rotating tool to generate frictional heat which mechanical stirring to create a defect-free weld. In this particular study, square tooltip and aluminum alloy AA6061 as workpiece are the material used. The aim is to investigate the effect of different welding parameters, specially the welding speed of 1055 rpm, 1320 rpm 1640 rpm, 1930 rpm, and 2620 rpm, while maintaining a constant federate of 14 mm/min. Tensile testing are performed to assess the mechanical properties of material including strength and ductility as the process were subjected tensile forces until failure occurred. As for Vickers hardness was employed to assess the hardness distribution in 3 different regions of welded area. Microstructure analysis are done by optical microscopy allowed for visualize of grain boundaries, orientations and potential defect present in the welded area. For scanning electron microscopy (SEM) was employed of more detailed microstructure analysis which able to generate dimple boundaries and intermetallic compounds. By varying the rotational speed of tool, different results in terms of mechanical properties and microstructure are obtained.